Does Sensory Function Decline Independently or Concomitantly with Age? Data from the Baltimore Longitudinal Study of Aging. (27th September 2016) - Gadkaree, Shekhar K.; Sun, Daniel Q.; Li, Carol; Lin, Frank R.; Ferrucci, Luigi; Simonsick, Eleanor M.; Agrawal, Yuri
Abstract : Objectives . To investigate whether sensory function declines independently or in parallel with age within a single individual. Methods . Cross-sectional analysis of Baltimore Longitudinal Study of Aging (BLSA) participants who underwent vision (visual acuity threshold), proprioception (ankle joint proprioceptive threshold), vestibular function (cervical vestibular-evoked myogenic potential), hearing (pure-tone average audiometric threshold), and Health ABC physical performance battery testing. Results . A total of 276 participants (mean age 70 years, range 26–93) underwent all four sensory tests. The function of all four systems declined with age. After age adjustment, there were no significant associations between sensory systems. Among 70–79-year-olds, dual or triple sensory impairment was associated with poorer physical performance. Discussion . Our findings suggest that beyond the common mechanism of aging, other distinct (nonshared) etiologic mechanisms may contribute to decline in each sensory system. Multiple sensory impairments influence physical performance among individuals in middle old-age (age 70–79).